Yield of eggplant using low quality water and pulse drip irrigation - Stephanie S. Arriero; Willian F. de Almeida; Vital P. da S. Paz; Lucas F. Damasceno (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The use of saline water and wastewater in agriculture has been increasingly considered, and this is due to the increase in awareness about the conservation of natural resources and population growth, implying a greater demand for food. Drip irrigation already has many benefits and, with the splitting of the depths to be applied, results in pulse drip irrigation, which further favors the plant by providing more constant moisture in the soil. The objective of this study was to evaluate the effects of the application of wastewater and saline water by pulse drip irrigation on eggplant yield and water use efficiency. The experimental design was randomized blocks in 2 x 5 factorial scheme, corresponding to continuous and pulse drip irrigation and five types of water (municipal, saline (sodium chloride), saline (calcium chloride), wastewater, and a mix of saline (sodium chloride) and wastewater), with five repetitions. Water use efficiency was quantified according to the water applied and the production. Pulse drip irrigation promoted higher marketable fruit yield. The best performance of eggplant was verified when wastewater was applied via pulse drip irrigation. Wastewater via pulse drip irrigation can be used to grow eggplant for higher marketable yield and water use efficiency.